PERANCANGAN SISTEM INFORMASI PERSEDIAAN SUKU CADANG UNTUK ALAT BERAT BERBASIS DESKTOP PADA CV BATAM JAYA - Seah, Jonny; Ridho, Muhammat Rasid (Computer Science and Industrial Engineering, 2020)
Inventory is one of most important asset which the data collection must be managed and saved with good condition by the company. It is likewise happen at CV Batam Jaya, a company that serve rental for heavy equipment keeps many kinds of spare parts which is can't be fully memorized with head. That inventory data management still applied in a manual method, such as write the name, the specification, and the quantity on the particular book. Indeed, that method provokes a bunch of problems like have a high possibility on cause inaccurate data content, data loss and no back-up, so the other job can be hampered. the purposes of this research are to contrive and build a computerized inventory information system because system that controlled by computer may escalate the effectiveness and the flexibility of managing, finding the data easily and quickly. research that involving formalization of the matter until system design will be held by using System Development Life Cycle (SDLC) with Waterfall Model, whilst the system development will be done by making some interfaces in accordance with the design that made by Unified Model Language (UML) model. The development also followed by object oriented-programming using Visual Studio 2019 and MySQL for the database. the expectation of this project is by having an inventory information system, conservation of the storage becomes more thrifty and have a simple data management.